KEANEKARAGAMAN VEGETASI MANGROVE (STUDI KASUS DI DESA KALIKUR WAIKORO LEULALENG, KECAMATAN BUYASURI, KABUPATEN LEMBATA, PROVINSI NUSA TENGGARA TIMUR) - Ikujram Goasyah; Maria M. E. Purnama; Nixon Rammang (Wana Lestari, 2021)
This Research was conducted to determine the diversity of Mangrove vegetation. This Research was conducted in Kalikur Vilage, Waikoro Leulaleng, Buyasuri District, Lembata Regency, East Nusa Tenggara Province. It Was conduted for 1 month, from September to October 2020. This study used the Vegetation Analysis method, transect track, and interviews with data analysis using qualitative descriptive analyisis and quantitative descriptive analysis. The data was processed using the Shannon Wiener (H’) diversity index formula. The results showedthe Mangrove vegetation found ther were 4 types of Mangrovethat is Sonniratia alba, Rhizophora apiculata, Rhizophora mukronata, and Bruguiera gymnoriza. Based on vegetation analysis shows the value of density, frequency, dominance and INP values of Sonniratia alba type is higher than the other type. This shows that Sonniratia alba is able to adapt to the environment. The results of the Mangrove type of calculation of observation showed the diversity of types at all levels indicates disruption and pressure by outer factors due to the upset of tidal causes that causes the body’s mechanich to unfluence bad, and distrub the exchange of gas, soil water and the atmosphere.